THE EXISTENCE OF FUNGI AND THE EFFECT OF TERMINAL CLEANSING ON OPERATING ROOM AIRBORNE FUNGI - Firdaus, Nadilla Shafa; Farida, Helmia; Hapsari, Rebriarina (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Fungi is one of the causes of infectious diseases, especially in immunocompromised patients. Surgical site infection (SSI) becomes a major challenge as it is the leading cause of healthcare-associated infection (HAIs). HAIs can be caused by endogenous or exogenous fungi. Exogenous fungi are present in the hospital environment, such as airborne fungi. Fungal contamination of the operating area occurs during surgery or after surgery. The effect of temperature, humidity, the focus of fungal source, and room cleanliness can trigger the growth of fungi in the operating room.  Aim: To analyse the growth of fungal air contamination and its affecting factors in the operating room of a type C hospital. Methods: This study used analytic observational with a cross-sectional design. Total samples were 5 operating rooms that were not in repair. Sampling was using the settle down plate 1/1/1 method. The plates of each replication in each room were 13 plates. The fungal culture was at the temperature of 25⁰C and was observed with LPCB. Measurement of temperature and humidity was using the thermo-hygrometer. The focus of the fungal sources was observed in the ceiling of the operating room. Results: In a total of 5 operating rooms, the Fisher exact test results showed no significant differences between room cleaning and fungal growth in the air (p=0.400). In the primary data, the most fungal growth in operating room number 1 and number 5 was 5 plates. The decline in the number of plate overgrown occurred in the operating room number 1, from 5 plates to 1 plate. The Fisher exact test result showed no significant differences between temperature, humidity, and the focus of fungal source with fungal growth in the air (p=1).  Conclusion: In this study, room cleaning, temperature, humidity, and the focus of the fungal source showed no effect on the fungal growth in the air.